Regenerative Medicine of Liver: Promises, Advances and Challenges - Saiful Ali; Nasira Haque; Zohya Azhar; Morvarid Saeinasab; Farshid Sefat (Biomimetics, 2021)
Liver tissue engineering is a rapidly developing field which combines the novel use of liver cells, appropriate biochemical factors, and engineering principles, in order to replace or regenerate damaged liver tissue or the organ. The aim of this review paper is to critically investigate different possible methods to tackle issues related with liver diseases/disorders mainly using regenerative medicine. In this work the various regenerative treatment options are discussed, for improving the prognosis of chronic liver disorders. By reviewing existing literature, it is apparent that the current popular treatment option is liver transplantation, although the breakthroughs of stem cell-based therapy and bioartificial liver technology make them a promising alternative.